HALDUN TANER`İN HİKAYELERİ VE HİKAYECİLİĞİ ÜZERİNE BİR İNCELEME - BAYRAK, ÖZCAN (Fırat Üniveristesi, 2002)
[Abstract Not Available]
A Research on Haldun Taner`s stories and his narration
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature